Effect of oxygen ion energy and annealing in formation of tin oxide thin films - Song, SK; Choi, WK; Cho, JS; Jung, HJ; Choi, D; Lee, JY; Baik, HK; Koh, SK (JAPAN J APPLIED PHYSICS, 1997)
Tin oxide (SnOx) thin films were deposited by ion-assisted deposition (IAD) at various ion beam voltages (V-I) onto amorphous SiO2/Si substrate at room temperature. Tin oxide thin films with nonstoichiometric/stoichiometric composition were fabricated. The as-deposited SnOx films were mostly amorphous, but they exhibited various degrees of crystallinity and fine grain size after annealing at 500 degrees C for Ih in air. The annealed film deposited using an ion beam energy (E-I) of 300 eV showed a preferred orientation along the SnO2 (110) plane. The preferred orientation changed to SnO2 (002) for film 1000 (the annealed film deposited with E-I = 1000 eV) through an amorphous intermediate structure of film 500 (the annealed film deposited with E-I = 500 eV). X-ray photoelectron spectroscopy study showed that the main Sn3d peaks in all samples were similar to the binding energy of Sn4+ and the atomic ratios for all the films were higher than 1.51. For the film grown under an average energy of 123 eV/atom, the refractive index was 2.0 and the estimated porosity was 5.2% smaller than that of the other films.